Service quality perceptions between cooperative and Islamic banks of Britain - Sadek, Daing Maruak; Zainal, Noor Saliza; Mohd Taher, Muhammad Saiful Islami; Yahya, Ahmad Fauzi; Shaharudin, Mohd Rizaimy; Noordin, Nazni; Zakaria, Zaherawati; Jusoff, Kamaruzaman (Science Publications, 2010)
Problem statement: The objectives of this study were to determine mean comparison all 6 dimensions between Cooperative Bank (CB) and Islamic Bank of Britain (IBB) in Leicestershire, United Kingdom, to compare the ranking for CB and IBB based on the customers preference and lastly to identify the similarities between CB and IBB based on customer preference. Approach: A sample of retail banking customers from CB and IBB was surveyed through a set of questionnaires. The proposed scale is called SERVQUAL and comprises 33 items named ‘CARTER’ with six dimensions (Compliance, Assurance, Reliability, Tangible, Empathy and Responsiveness), which customized for suitability of CB and IBB. The data was analyzed based on SPSS. Results: The study indicated that the mean comparison for all 6 dimensions were compared and shown that the Compliance issues were very important for IBB customers, while the same cannot be mentioned for the CB customers, who gave more importance to Empathy and Responsiveness. On the other hand, the highest ranked between IBB and CB were found, where the customers of IBB chose No interest paid nor taken on saving and loan as a preferred items and CB customers more preferred to chose Run on ethical value as the highest rank. The results also demonstrated that the similarities were found where almost of the items in Assurance have a similar ranking in both of banks. Conclusion/Recommendations: Future research should be conducted with a big number of respondents to ensure the representative and conclusive finding. Next, the new research needs to increase a number of banks to obtain the good result.